Pengaruh Minat Belajar Mahasiswa Tata Rias terhadap Hasil Praktik Rias Pengantin Solo Putri - Kuswidyaningrum NJ; Aulia Romadona (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Solo Putri bridal makeup is a type of traditional makeup that requires precision, patience, and high technical skills. The level of student interest in learning reflects the extent of their interest and seriousness in understanding a learning material. This study aims to examine the influence of learning interest on the results of Solo Putri bridal makeup practice among students in the AKS Ibu Kartini Semarang Makeup Design Program, using a quantitative approach through simple linear regression. The research subjects consisted of 30 students, and the instruments used included a learning interest questionnaire and a practice results assessment sheet. Data were analyzed using normality, linearity, and simple linear regression tests. The analysis results showed a positive and significant correlation between learning interest and students' practical results. The correlation coefficient (R) value of 0.794 and the coefficient of determination (R²) of 0.630 indicate that learning interest has a significant contribution to the success of bridal makeup practice. The higher the learning interest of students, the higher the quality of practice results achieved. Therefore, learning interest is an important aspect that requires attention in practical learning. Effective learning strategies such as contextual approaches, project-based learning, and the provision of adequate practical facilities need to be implemented.